1998
DOI: 10.1023/a:1006914301565
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: It was found that both normal human myometrium and uterine leiomyoma contain several glycosaminoglycans. In contrast to many normal and tumour tissues the amount of hyaluronic acid is very low and the proportional amount of sulphated glycosaminoglycans is distinctly higher. It is of interest that heparan sulphate is the major glycosaminoglycan component both in normal myometrium, and in leiomyoma. The amount of hyaluronic acid in myometrium and in the leiomyoma is very low. No significant change in hyaluronate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 21 publications
0
13
0
2
Order By: Relevance
“…The most common symptom is abnormal bleeding which may require surgical removal of the uterus due to symptom severity (Walker and Stewart, 2005; Sabry and Al-Hendy, 2012). The tumors are composed of excessive extracellular fibrous proteins including the collagens, proteoglycans and glycosamines (Wolańska et al, 1998; Nowak, 2001; Malik et al, 2010). It is the excessive amount of extracellular matrix (ECM) secreted by the leiomyoma cells that makes up the tumor bulk resulting in symptoms (Fujita, 1985; Wolańska et al, 1998; Mitropoulou et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common symptom is abnormal bleeding which may require surgical removal of the uterus due to symptom severity (Walker and Stewart, 2005; Sabry and Al-Hendy, 2012). The tumors are composed of excessive extracellular fibrous proteins including the collagens, proteoglycans and glycosamines (Wolańska et al, 1998; Nowak, 2001; Malik et al, 2010). It is the excessive amount of extracellular matrix (ECM) secreted by the leiomyoma cells that makes up the tumor bulk resulting in symptoms (Fujita, 1985; Wolańska et al, 1998; Mitropoulou et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The tumors are composed of excessive extracellular fibrous proteins including the collagens, proteoglycans and glycosamines (Wolańska et al, 1998; Nowak, 2001; Malik et al, 2010). It is the excessive amount of extracellular matrix (ECM) secreted by the leiomyoma cells that makes up the tumor bulk resulting in symptoms (Fujita, 1985; Wolańska et al, 1998; Mitropoulou et al, 2001). Proteins of the matrix bind to transmembrane cell surface adhesion receptors, called integrins, that connect the ECM to the intracellular actin cytoskeleton and via signaling molecules initiate intracellular cascades which control cell shape, migration, proliferation, differentiation and survival (Giancotti and Ruoslahti, 1999; Belkin and Stepp, 2000; Miranti and Brugge, 2002; Schwartz and Ginsberg, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Prolidase activity is related to the pathogenesis of various diseases Savas et al 2010;Sezen et al 2010;Toy et al 2009aToy et al , 2010Vural et al 2010b;Yildiz et al 2008a). Since its property of representation of collagen turnover, prolidase is an important marker for tumour size and aggression of the fi broid growth (Wolanska et al 2001). …”
Section: Introductionmentioning
confidence: 99%
“…It is believed that indeed, the pathogenesis of leiomyomas at the cellular and molecular levels involves the interactions of cytokines/growth factors, as well as ECM components, that all play a pivotal role in the development of these tumors [26]. Furthermore, it has been suggested that some of the sulphated glycosaminoglycans (GAGs), such as heparan sulfate and heparin in the ECM, are involved in creating a storage depot for biologically active molecules, such as growth factors and enzymes, and under conditions of hydrolytic degradation of the GAGs there may be a release of cytokines and other factors that may promote tumor cell growth and stimulate collagen biosynthesis [27]. In this study, we found that many of the growth factors associated with proliferation and fibrogenesis, such as EGF, TGF-β1, TGF-β3, VEGF, FGF-2, and PDGF-A and -B were increased in the media of cocultured UtLM cells, which suggested that these soluble factors are capable of stimulating the proliferation of UtLM cells and collagen I production.…”
Section: Discussionmentioning
confidence: 99%